Hydration and temperature in tennis - A practical review - Kovacs, M. S. (Journal of Sports Science & Medicine, 2006)
Competitive tennis is typically played in warm and hot environments. Because hypohydration will impair tennis performance and increases the risk of heat injury, consumption of appropriate fluid levels is necessary to prevent dehydration and enhance performance. The majority of research in this area has focused on continuous aerobic activity - unlike tennis, which has average points lasting less than ten seconds with rest periods dispersed between each work period. For this reason, hydration and temperature regulation methods need to be specific to the activity. Tennis players can sweat more than 2.5 L·h-1 and replace fluids at a slower rate during matches than in practice. Latter stages of matches and tournaments are when tennis players are more susceptible to temperature and hydration related problems. Sodium (Na+) depletion, not potassium (K+), is a key electrolyte in tennis related muscle cramps. However, psychological and competitive factors also contribute. CHO drinks have been shown to promote fluid absorption to a greater degree than water alone, but no performance benefits have been shown in tennis players in short matches. It is advisable to consume a CHO beverage if practice or matches are scheduled longer than 90-120 minutes.